2007
DOI: 10.1901/jaba.2007.697-701
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Intraverbal Antonyms in Children With Pervasive Developmental Disorder

Abstract: In the type of intraverbal that consists of saying the opposite of a word, two intraverbals are related to one another because the response form of each intraverbal functions as part of a discriminative stimulus for the other (e.g., ''cold'' in response to ''name the opposite of hot,'' and vice versa). Moreover, the contextual cue ''Name the opposite of -'' is the same in the two intraverbals. The purpose of the present research was to explore a procedure designed to promote emergence of intraverbals of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 3 publications
2
26
1
1
Order By: Relevance
“…Relevant academic instruction (for a seminal review, see Stromer et al, 1992) has, therefore, focused on basic academic repertoires such as translating between fractions and decimals (Lynch & Cuvo, 1995), identifying letters (Connell & Witt, 2004;Lane & Critchfield, 1998a) or words (de Rose, de Souza, & Hannah, 1996), and translating between English and Spanish words (Joyce & Joyce, 1993). In recent years, applications also have emerged that focus on basic social and communicative abilities (e.g., Pérez-González, García-Asenjo, Williams, & Carnerero, 2007;Rosales & Rehfeldt, 2007).…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…Relevant academic instruction (for a seminal review, see Stromer et al, 1992) has, therefore, focused on basic academic repertoires such as translating between fractions and decimals (Lynch & Cuvo, 1995), identifying letters (Connell & Witt, 2004;Lane & Critchfield, 1998a) or words (de Rose, de Souza, & Hannah, 1996), and translating between English and Spanish words (Joyce & Joyce, 1993). In recent years, applications also have emerged that focus on basic social and communicative abilities (e.g., Pérez-González, García-Asenjo, Williams, & Carnerero, 2007;Rosales & Rehfeldt, 2007).…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…in contrast the studies in the area of verbal behavior cited here used topographybased operants but also combined topography-based with selection-based operants. The only exceptions were the studies by Pérez-González, García-Asenjo, et al (2007) and by Polson and Parsons (2000) cited above, which were conducted exclusively with intraverbals. Moreover, researchers in the area of verbal behavior have not studied emergence of verbal relations with the A-B-C format of stimulus equivalence.…”
mentioning
confidence: 99%
“…Studies of stimulus equivalence and stimulus relations have shown that when typically developing human beings are taught a few stimulus-stimulus relations, other nontaught stimulusstimulus relations typically emerge. The basic procedure of stimulus 1985; Lipkens, Hayes, & Hayes, 1993;Luciano, 1986;Partington & Bailey, 1993;Pérez-González, García-Asenjo, Williams, & Carnerero, 2007;Polson & Parsons, 2000;Sundberg & Sundberg, 1990;Twyman, 1996;Watkins, PackTeixteira, & Howard, 1989). For example, Polson and Parsons taught college students to type English words in the presence of their corresponding French words (a skill of a paired-associates-type procedure that is an intraverbal) and probed whether the students typed the French words in the presence of the corresponding English words.…”
mentioning
confidence: 99%
“…Four of the five participants who passed the matching-to-sample (MTS) tests (out of 10) did so without emitting the symmetrical intraverbal, challenging the naming hypothesis. Of note, baseline tact and intraverbal relations were slowly acquired, which would suggest that participants may have not had a sufficiently sophisticated verbal repertoire to derive bi-directional (i.e., symmetrical) intraverbals-a skill shown to be brought about after a history of multiple-exemplar training (Pérez-González et al 2007). Thus, it is possible that the participants in Pettursdottir et al…”
mentioning
confidence: 99%